Analysis of the COVID-19 vaccine willingness and hesitancy among parents of healthy children aged 6 months–4 years: a cross-sectional survey in Italy - Postiglione, Mario; Miraglia del Giudice, Grazia; Della Polla, Giorgia; Angelillo, Italo Francesco (Frontiers in Public Health, 2023)
Introduction In Italy, since December 2022, the COVID-19 vaccination has been extended to children aged 6 months–4 years with conditions of fragility and to those healthy at the request of the parent. The purposes of the cross-sectional survey were to determine the willingness and hesitancy of the parents/guardians to have their healthy children vaccinated against COVID-19. Methods The survey was performed among 389 parents/guardians with a child aged 6 months–4 years randomly selected from seven kindergartens and eight nursery schools in the geographic area of Naples, Italy. Results Only 10.5% were very concerned about the risk of infection, and the mean values regarding the perceived utility and safety of the COVID-19 vaccine were 3.3 and 3.2, respectively. Only 13.7% of participants were willing to consent to vaccinate the selected child against COVID-19, while 20.1% were uncertain and 66.2% did not intend. Parents/guardians of older children, those who received information about the COVID-19 vaccine from physicians or pediatricians, those who believed that the COVID-19 vaccine was useful, and those with lower hesitancy regarding the COVID-19 vaccine were more willing to vaccinate their child. The mean Parent Attitudes About Childhood Vaccines (PACV-5) score was 5.6, with 33.1% of respondents who were identified as highly hesitant toward COVID-19 vaccination (score ≥ 7). Parents/guardians with a lower perceived safety of the COVID-19 vaccine were more likely to be highly hesitant. Discussion The findings reveal the need to improve community-based education campaigns and effective promotion of the COVID-19 vaccination to increase willingness and address parental safety concerns.